1995
DOI: 10.1111/j.1525-1446.1995.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Peer Counseling: An Answer to the Persistent Difficulties with Prenatal Care for Low‐Income Women

Abstract: Our intention in this article is to provide the reader with the theoretical framework of prenatal peer counseling. A second article describing a prenatal peer program that is functional in the province of Quebec will be presented subsequently with its outcomes and recommendations. However, before planning the implementation of such a program or even assessing its effectiveness, one must understand how peer counseling can be used as an assistive strategy and why it is perceived to be a community approach worth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Prenatal programmes involving paraprofessional outreach workers or peer counsellors also have been found to be acceptable to disadvantaged women ( Bell Woodard & Edouard 1992, McFarlane & Fehir 1994). It is postulated that peer counselling is congruent with the specific needs of pregnant women from poor socio‐economic backgrounds because it can foster empowerment, thereby contributing to increased self‐esteem, reduced anxiety and improved self‐care ( Lapierre et al. 1995 ).…”
Section: The Concept Of Barriersmentioning
confidence: 99%
“…Prenatal programmes involving paraprofessional outreach workers or peer counsellors also have been found to be acceptable to disadvantaged women ( Bell Woodard & Edouard 1992, McFarlane & Fehir 1994). It is postulated that peer counselling is congruent with the specific needs of pregnant women from poor socio‐economic backgrounds because it can foster empowerment, thereby contributing to increased self‐esteem, reduced anxiety and improved self‐care ( Lapierre et al. 1995 ).…”
Section: The Concept Of Barriersmentioning
confidence: 99%
“…Research has shown a higher incidence of infant morbidity in single mothers (Taffel, 1990), black mothers (Leland, Petersen, Braddock, & Alexander, 1995;Geronimus, 1987;Ingram, Makuc, & Kleinman, 1986;Kleinman, 1990;Taffel, 1990), low-income mothers (Brook, 1980;MacMahon, 1982;Stockwell, Swanson, & Wicks, 1988;Taffel, 1990), and high school dropouts (Kappelman, Khan, Washington, Stine, & Cornblath, 1974;Taffel, 1990). Maternal education has also been found to be related positively to MD prenatal care (Schaefer & Hughes, 1976;Taffel, 1990).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…To date it remains unknown whether the contents of the PHN contact or simply the contact itself is associated with positive outcomes. Although a few prenatal programs (LaPierre, Perreault, & Goulet, 1995;May, McLaughlin, & Penner, 1991;Skovholt, Lia-Hoagberg, Mullett, Siiteri, Vanman, Josten, McKay, & Oberg, 1994) have used community outreach workers in this manner, the effectiveness of these workers has not been well documented.…”
Section: Phn Contact and Birthweightmentioning
confidence: 99%
“…information providers, interpreters, and navigators of complicated health care systems Eng, Parker, & Harlan, 1997;Israel, 1985!. Researchers report that CHW programs that traditionally mentored low-income pregnant women and mothers who had young children have been expanded to encompass all at-risk women~Lapierre, Perreault, & Goulet, 1995;Larson McGuire, Watkins, & Mountain, 1992;Main, 1997!. CHWs increasingly bridge the gaps between health care providers and women who may not trust or feel comfortable with their health plan or doctors, do not realize they need routine health care, and0or choose to receive no health care for social or cultural reasons~Eng & Young, 1997!. Programs have been developed to increase decision-making skills and self-sufficiency among low-income women~Main, 1997;Warrick Wood, Meister, & de Zapier, 1992;Watkins, Larson, Harlan, & Young, 1990!, to increase social support networks~Sue et al, 1994!, to promote prosocial skills and attitudes~Richey, Lovell, & Reid 1991!, to provide wellness programs~Earp, 1997Holden Consulting, 1999;Sung et al, 1997;Thomas, Eng, Clark, Robinson, & Blumenthal, 1998!, and to give informal social support via weekly home visits and participation in parenting groups~Dawson, Robinson, Butterfield, & Van Doorninck, 1991!. Studies that focused on the use of CHWs in combination with other resources have revealed the positive effects of CHWs, not only on low-income pregnant women and mothers with young children, but also on the communities in which they livẽ McFarlene & Fehir, 1994!.…”
mentioning
confidence: 99%